Eine Bilanz zur Integration digitaler Medien an Grundschulen in Deutschland aus international vergleichender Perspektive - Eickelmann, Birgit (Neue Medien in der Grundschule 2.0. Grundlagen - Konzepte - Perspektiven)

High-stakes testing and Educational Governance – Insights and innovations in European school systems. Special Issue Editorial - Lorenz, Ramona; Eickelmann, Birgit; Bos, Wilfried (Journal for Educational Research Online (JERO))

Schulische Innovationen im Kontext digitaler Bildung – eine Betrachtung aus der Lehrerperspektive - Gerick, Julia; Eickelmann, Birgit (Zeitschrift Schul-Management)

Digital natives or just kids with smartphones? - The story of ICILS in Germany - Eickelmann, Birgit (IEA Newsletter)

Zur Relevanz informatischer Bildung in der Schule für den Erwerb computer- und informationsbezogener Kompetenzen als Teil von Medienbildung – Ergebnisse für Deutschland und die Schweiz im internationalen Vergleich - Eickelmann, Birgit; Drossel, Kerstin (Zeitschrift MedienPädagogik)

Schule digital – der Länderindikator 2016. Kompetenzen von Lehrpersonen der Sekundarstufe I im Umgang mit digitalen Medien im Bundesländervergleich

Kooperation von Lehrkräften der Sekundarstufe I zum Einsatz digitaler Medien in Lehr- und Lernprozessen in Deutschland und im Bundesländervergleich - Welling, Stefan; Lorenz, Ramona; Eickelmann, Birgit (Schule digital – der Länderindikator 2016. Kompetenzen von Lehrpersonen der Sekundarstufe I im Umgang mit digitalen Medien im Bundesländervergleich)

Die eingeschätzte Relevanz der Phasen der Lehrerausbildung hinsichtlich der Vermittlung didaktischer und methodischer Kompetenzen von Lehrpersonen für den schulischen Einsatz digitaler Medien in Deutschland und im Bundesländervergleich - Eickelmann, Birgit; Lorenz, Ramona; Endberg, Manuela (Schule digital – der Länderindikator 2016. Kompetenzen von Lehrpersonen der Sekundarstufe I im Umgang mit digitalen Medien im Bundesländervergleich)

Additive Fertigungsverfahren im Kontext von Industrie 4.0 - Klemp, Eric; Pottebaum, Jens (Handbuch Industrie 4.0 Bd.3)

Fatigue crack growth behavior and mechanical properties of additively processed EN AW-7075 aluminium alloy - Reschetnik, Wadim; Brüggemann, Jan-Peter; Aydinöz, Mehmet Esat; Grydin, Olexandr; Hoyer, Kay-Peter; Kullmer, Gunter; Richard, Hans Albert (Procedia Structural Integrity)

Stochastic recursive inclusion in two timescales with an application to the lagrangian dual problem - Ramaswamy, Arunselvan; Bhatnagar, Shalabh (Stochastics)

Dokumentenorientierte NoSQL-Datenbanken in skalierbaren Webanwendungen - Eine Analyse am Beispiel von MongoDB und der Webanwendung PINGO - Bach, Christoph; Kundisch, Dennis; Neumann, Jürgen; Schlangenotto, Darius; Whittaker, Michael (HMD Praxis der Wirtschaftsinformatik)

Grundsatzfragen der Abwärmenutzung. Effizienzsteigerungspotenziale in der Industrie durch Abwärmenutzung erschließen. - Philipp, Matthias; Schumm, Gregor; Schlosser, Florian; Hechelmann, Ron-Hendrik; Holzhammer, Uwe (BWK Energie-Fachmagazin)

Hybrid-heating-systems for optimized integration of low-temperature-heat and renewable energy - Schumm, Gregor; Philipp, Matthias; Schlosser, Florian; Hesselbach, Jens; Walmsley, Timothy G.; Atkins, Martin J. (Chemical Engineering Transactions)

Hardware in the Loop Evaluation of a Hybrid Heating System for Increased Energy Efficiency and Management - Schumm, Gregor; Philipp, Matthias; Schlosser, Florian; Hesselbach, Jens; Walmsley, Timothy G.; Atkins, Martin J.

Stackelberg Competition among Intermediaries in a Differentiated Duopoly with Product Innovation - Manegold, Jochen
On an intermediate goods market we consider vertical and horizontal product differentiation and analyze the impact of simultaneous competition for resources and the demand of customers on the market outcome. Asymmetries between intermediaries may arise due to distinct product qualities as well as by reasons of different production technologies. The intermediaries compete on the output market by choosing production quantities sequentially and for the supplies of a monopolistic input supplier on the input market. It turns out that there exist differences in product quality and productivities such that an intermediary being the Stackelberg leader has no incentive to procure inputs, whereas in the role of the Stackelberg follower will participate in the market. Moreover, we find that given an intermediary is more competitive, his equilibrium output quantity is higher when being the leader than when being the follower. Interestingly, if the intermediary is less competitive and goods are complements, there may exist asymmetries such that an intermediary being in the position of the Stackelberg follower offers higher output quantities in equilibrium than when being in the position of the Stackelberg leader.
Keywords: Input Market; Product Quality; Quantity Competition; Stackelberg Competition; Product Innovation

Modelling of temperatures and heat flow within laser sintered part cakes - Josupeit, Stefan; Ordia, Lavish; Schmid, Hans-Joachim (Additive Manufacturing)
Temperature effects in the polymer laser sintering process are an important aspect regarding the process reproducibility and part quality. Depending on the job layout and position within the part cake, individual temperature histories occur during the process. Temperature history dependent effects are for example part warpage, the crystallization rate and powder ageing effects. This work focuses on temperatures and heat flow within laser sintered part cakes. Therefore, a thermal Finite Element (FE) model of a part cake is developed based on experimental in-process temperature measurements. Thermal boundary conditions and properties of the used bulk polymer powder are analyzed and relevant parameters are identified. The model is validated and optimized considering different job heights and ambient conditions during the cooling phase. It is finally possible to predict position-dependent temperature histories as a function of significant job parameters. The model allows a transfer of the results for varied boundary conditions during cooling. In combination with an implementation of built parts, this model will be an important tool for the development of optimized process controls and cooling strategies.

Guard ring induced distortion of the steady velocity profile in a parallel plate rheometer - Schmid, Hans-Joachim; Pieper, S. (Applied Rheology)
The shape and fracture of the free surface frequently limits the measuring range and impedes the use of optical velocimetric techniques in parallel plate and cone plate setups. To prevent this, various kinds of edge guards are often employed. In the present study, we elucidate how an edge guard distorts the steady velocity profile in a parallel plate setup. To this end, we analyzed the velocity field of a strongly shear-thinning fluid, a Newtonian fluid and a set of suspensions via particle image velocimetry in a parallel plate device. Several guard ring sizes were studied. The distortion is described by a simple three parameter model. These parameters are mostly constant for different fluids and suspensions with particle volume fractions below 45%. With increasing radius, the guard ring.s influence approaches a limiting value that we attribute to the influence of the fluid surrounding the gap. Our results indicate a limiting ratio of the difference between plate radius and guard to gap size that should always be exceeded. In the presence of a guard ring, even Newtonian fluids do not exhibit a constant shear rate for most radial distances within the gap. This distortion of the velocity field challenges the simple superposition approach of unguarded device and guard influence that is prevalent in the literature.

Layer-formation of non-colloidal suspensions in a parallel plate rheometer under steady shear - Pieper, Sven; Schmid, Hans-Joachim (Journal of Non-Newtonian Fluid Mechanics)
Suspensions are subject to confinement induced structuring, i.e. layering, at the confining surfaces. While most of the previous work focused on layering in Couette cells, the present study aimed to characterize the resulting layers at the plates of a parallel plate rheometer with regard to their relative particle concentration. The particle concentration profile over the radial distance was characterized for various mean concentrations and gap heights. To this end, we mapped the distribution of fluorescently dyed tracer particles in density and refractive index matched suspensions. The results indicate that layering at the surfaces stabilizes as the ratio between gap height and particle diameter increases. For lower gap heights, i.e. as the suspension approaches a two dimensional state, the layer concentration was non-uniform over the plates. In general, results were quantitatively different for the upper and lower plate and the concentration profiles were noticeably asymmetric. We conclude that this is probably the result of the rheometer loading or the start-up process. The stable layers as well as the inhomogeneous particle distribution in general offer an explanation for the lack of transferability of viscosimetric results between different setups.

Auswahl internationaler Standorte - Wie lassen sich Standortentscheidungen methodisch unterstützen? - Betz, Stefan (ForschungsForum Paderborn)